Integrated Approach of Unit Trust and Waqf as Sustainable Investment Conceptual Model in the Covid-19 Era - Sulaiman, Syahnaz; Hasan, Aznan (USIM Press, Universiti Sains Islam Malaysia, 2020)
Harnessing a sustainable model of waqf remains as the key challenge faced by waqf managers particularly in the mid of socio-economic crisis due to COVID-19 pandemic. This paper aims to present the viability of unit trust waqf as an alternative asset for waqf creation. This study employed a qualitative research designed through the use of document analysis of classical Islamic books, Islamic ruling (fatwa), journal articles, books, online resources, and policy documents. The novelty of this paper lies in its attempt to highlight the importance of waqf investment strategy in ensuring sustainable returns for waqf particularly during this difficult time in reducing the socioeconomic impact of COVID-19 catastrophe, by introducing conceptual model of unit trust waqf as potential mechanisms to pool more cash waqf from individual investors. This paper submitted that waqf plays a significant role as global financial cure for economic revival post COVID-19. The sustainability of the capital waqf assets in the form of unit trust is preserved through the distinctive fixed price feature of the unit trust waqf as proposed toward the end of the paper.